Career Counseling To Prepare For The World of Work - Mika Kuswanti; Cica Yulia (Publikasi Indonesia, 2023)
Career counseling is directly related to problems regarding the future of vocational school students in determining and choosing jobs based on all career attitudes they have. Career counseling is presented to provide services in shaping the career patterns of vocational school students towards the world of work. The purpose of this article is to conduct a literature review on the implementation of career counseling in vocational schools and university in several countries for preparation for the world of work. In the process of collecting data, 7 journals were found that support this research. The results of the study found that the implementation of career counseling in vocational schools has different way. Career counseling is something that supports job readiness in addition to the self-concept that students already have. The results of this study can also be used as recommendations for career counseling officers in order to improve services and optimize the career counseling service system.